King and the other America : the Poor People's Campaign and the quest for economic equality - Laurent, Sylvie (University of California Press, 2018)
"Shortly before his assassination, Martin Luther King, Jr. called for a radical redistribution of economic and political power to transform the whole of society. A neglected and obscured episode of the late Civil Rights movement, The Poor People's Campaign, designed by King in 1967 and carried out after his death, brought together impoverished Americans of all races to demand better wages, better jobs, better homes, and better education. He believed that not only a fight for rights but the radical distribution of wealth had to be demanded through interracial protest. King and the Other America explores this overlooked campaign to not only understand King's commitment to social justice but to understand the long-term trajectory of the Civil Rights Movement. Digging into earlier 20th century arguments about economic inequality across America, which King drew on through his entire political and religious life, Sylvie Laurent argues that the Poor People's Campaign was the logical culmination of King's influences and ideas and the lasting impact he had on young activists and the public. Fifty years later, growing inequality and grinding poverty in the United States have spurred new efforts to rejuvenate the campaign. This book is essential to understanding today's movement through King's radical, intellectual thought and his struggle for genuine equality for all"--Provided by publisher.